Study of the drive mechanism of the working bodies of a roller machine - Amanov, Auezhan T.; Bahadirov, Gayrat A.; Nabiev, Ayder M.; Tsoy, Gerasim N.; Abdullajanov, Asrorbek A. (Edelweiss Applied Science and Technology, 2024)
A design of a roller machine with an improved drive mechanism of working bodies is developed in the article. The roller machine has expanded functionality when performing technological operations of dehydrating moisture-saturated fiber materials. The developed mechanism ensures stable and reliable operation of the drive of working bodies, regardless of the unevenness and variations in the parameters of the processed moisture-saturated fibrous materials, achieving synchronicity of the working body operation. The study aims to expand the functionality of the roller machine, ensure stable and reliable operation of working roller drives regardless of the unevenness and changes in the parameters of the processed moisture-saturated fibrous materials, and ensure synchronicity of the working rollers.